Vegetation feedback causes delayed ecosystem response to East Asian Summer Monsoon Rainfall during the Holocene - Jun Cheng (Nature Portfolio, 2021)
How the East Asian Summer Monsoon has changed over the Holocene has been debated, as some proxy records disagree with each other. Here, the authors suggest that monsoonal rainfall peaked in the early Holocene, while ecosystem responses peaked in the mid-Holocene, explaining the differences between records.